جدید دور میں زکوٰۃ اور عشر کے نظام کو فعال بنانے کے لیے ٹیکنالوجی کا استعمال: USE OF TECHNOLOGY TO ENABLE ZAKAT AND USHAR SYSTEM IN MODERN TIMES (Al-Aasar, 2025)
This research paper presents a detailed analysis of the use of technology to enhance the effectiveness of the Zakat and Ushr system in the modern era. Zakat and Ushr hold great significance in Islamic society for promoting social justice and economic development. However, in the present times, the Zakat and Ushr system faces several challenges. To address these challenges and make the system more effective, technology offers an excellent solution.The paper discusses various technologies such as blockchain, artificial intelligence, and mobile applications to improve transparency, accounting, and the distribution process in the Zakat and Ushr system. With the help of blockchain technology, the data related to Zakat and Ushr can be securely and transparently recorded. Artificial intelligence can be used to identify eligible beneficiaries and automate the distribution of Zakat and Ushr funds. Mobile applications can simplify the payment of Zakat and Ushr and improve access to related information.The paper also analyzes the current state of the Zakat and Ushr system in Pakistan and provides practical recommendations for its improvement. In addition, a comprehensive framework for the distribution of Zakat and Ushr funds has been developed.